User Experience Design Of Mobile Charity Application Using Design Thinking Method - Nadia Aulia; Septi Andryana; Aris Gunaryati (SISFOTENIKA, 2021)
The charity application is an application used by donors when donating goods easily and quickly in obtaining information on what items are needed, the donation process and clear information about containers. Based on these problems, the authors create a solution by designing the user experience of a mobile-based application that creates the final result in the form of a high-fidelity prototype. With this design, it can make it easier for donors to donate goods easily and quickly. The design process uses the design thinking method which consists of five stages, namely emphatic, define, ideate, prototype and testing. Testing or testing in this study achieves three aspects of UX Attributes that have been determined, namely effectiveness, efficiency and satisfaction by providing a task or mission and a system usability scale. In testing the three aspects by 40 testers, the average value of effectiveness is 85, efficiency 0.117533 goals / second and satisfication 73.3 with high acceptability, the grade scale is the same as C and the adjective rating is good.